Discovery of Yaozhuang Stock and Deep Ore Prospecting Implication for the Western Mangling Orefield in North Qinling Terrane, Central China - Fan, Peng; Xi, Aihua; Zhou, Bin; Chao, Xu; Yang, Wenbo; Sun, Jiaxin; Zhu, Hongyu; Wei, Li (Frontiers in Earth Science, 2022)
In the western Mangling orefield, the molybdenum (Mo) polymetallic deposits are closely related to the ore-bearing porphyry stocks (individual outcrop size: <1 km2). In this study, we have discovered several granitic stocks at Yaozhuang. Systematic petrologic, zircon U-Pb-Hf isotope and whole-rock geochemical studies show that both the granitic stocks of porphyritic granite (157 ± 2 Ma) and the intruding monzogranite dike (153 ± 1 Ma) were emplaced in the Late Jurassic. These granitic stocks are characterized by high SiO2 (66.83–75.63 wt%), high K2O (4.15–5.05 wt%), high Al2O3 (12.90–16.93 wt%), and low MgO (0.06–0.73 wt%) and are metaluminous to weakly peraluminous, being highly fractionated I-A-type transition granites. The content of the total rare Earth element (ΣREE) of the porphyritic granite (139.6–161.7 ppm) is lower than that of the monzogranite (151.4–253.6 ppm). The porphyritic granite has weakly negative Eu anomalies (Eu/Eu* = 0.77–0.93), whereas the monzogranite has weakly positive Eu anomalies (Eu/Eu* = 0.97–1.21) and are more enriched in light rare Earth elements. Both of them are enriched in large ion lithophile elements (LILEs, e.g., K, Rb, and Ba) but depleted in high-field-strength elements (HFSEs, e.g., Nb, Ta, Ti, Zr, and Hf). The zircon εHf(t) values of all the samples range from −16.1 to −6.9, and the two-stage model ages (tDM2) are 1.78–2.16 Ga. The magma may have originated from partial melting of the lower crust (more than 40 km in depth) caused by mantle-derived magma underwelling. The plutons and stocks were emplaced into the intersection of the early EW-trending faults and the late (Yanshanian) NE-trending faults. The fertile magma with high water content (H2O > 4%) and high oxygen fugacity (Delta FMQ > 1.5) indicates that the Yaozhuang area has significant potential for porphyry Mo polymetallic ore discovery.